2009
DOI: 10.1161/circimaging.108.834192
|View full text |Cite
|
Sign up to set email alerts
|

Aortopulmonary Collaterals After Bidirectional Cavopulmonary Connection or Fontan Completion

Abstract: Background-Aortopulmonary collaterals (APCs) have been associated with increased morbidity after the Fontan operation. We aimed to quantify APC flow after bidirectional cavopulmonary connections and Fontan completions, using phase-contrast MRI, and to identify risk factors for the development of APCs. Methods and Results-APC blood flow was quantifiable in 24 of 36 retrospectively analyzed MRI studies. Sixteen studies were performed after the bidirectional cavopulmonary connections (group A) and 8 after the Fon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
137
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(159 citation statements)
references
References 22 publications
10
137
2
1
Order By: Relevance
“…The flows in each individual pulmonary vein can also be measured and the difference between cumulative pulmonary vein flow and pulmonary arterial flow provide a quantification of aorto-pulmonary collateral burden [29]. An alternative technique to estimate the aorto-pulmonary collateral burden is the difference between the ascending aorta flow and total systemic venous flow [30].…”
Section: Flowsmentioning
confidence: 99%
“…The flows in each individual pulmonary vein can also be measured and the difference between cumulative pulmonary vein flow and pulmonary arterial flow provide a quantification of aorto-pulmonary collateral burden [29]. An alternative technique to estimate the aorto-pulmonary collateral burden is the difference between the ascending aorta flow and total systemic venous flow [30].…”
Section: Flowsmentioning
confidence: 99%
“…In the present setting, MRI catheterization is a unique tool that combines invasive pressures and VEC MRI-derived flow data that also account for collateral aortopulmonary blood flow. 3,16,28 For reliable assessment of the PVR in the Fontan circulation, which is very susceptible to changes in volume load, pulmonary pressures and blood flow were measured in our study simultaneously but not sequentially. The MRI method used in this study for measuring collateral blood flow was adopted from the work published by GrosseWortmann et al 3 and Whitehead et al 14 In these studies, collateral flow was estimated by 2 approaches.…”
Section: Blood Flow and Pvrmentioning
confidence: 99%
“…1,2 Other authors have reported significant left-to-right shunting through aortopulmonary collaterals. 3,4 Both factors may have a direct impact on the PVR that cannot be measured in the Fontan circulation by conventional techniques, such as thermodilution or oxymetry.…”
mentioning
confidence: 99%
“…In BDG circulation with decreased arterial oxygen saturation and ordinary inspiratory oxygen concentration, the effects of low oxygen fall into categories (2) and (3); in other words, the responses are mediated by the chemoreceptor and peripheral vessels and the effects of this pathway are considered as the same as in the previous publications. Hypoxia stimulates excitatory impulses from the chemoreceptor to the brainstem vasomotor center, and enhances systemic SNA.…”
Section: Sna Under Low-oxygen Conditionsmentioning
confidence: 99%